PENGARUH GAYA KEPEMIMPINAN DAN PENGEMBANGAN KARIR DENGAN KINERJA - Yumhi Yumhi (Universitas La Tansa Mashiro, 2016)
This correlational research is aimed at obtaining information related to possibility whether carrer is related by leadership style and carrer development. The research was conducted at the BAPPEDA by using survey method with correlational applied in testing hypothesis. Sevently five participants were selected as samples by boring sampling. The result indicate that carrer development has the greatest influence. Based on the finding it could be concluded that variation of the carrer development might have been related by the variation of leadership style and carrer develompnet. Therefore, leaderhip style and carrer development. Should be put into consideration in developing carrer